2015
DOI: 10.5040/9781350995017
|View full text |Cite
|
Sign up to set email alerts
|

Parental Human Capital and Effective School Management

Abstract: Education systems in developing countries are often centrally managed in a top-down structure. In environments where schools have different needs and where localized information plays an important role, empowerment of the local community may be attractive, but low levels of human capital at the local level may offset gains from local information. This paper reports the results of a four-year, large-scale experiment that provided a grant and comprehensive school management training to principals, teachers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Despite the widespread adoption of SBM, the effectiveness of these programs in raising educational outcomes have been mixed. Experiments in India (Banerjee et al, 2010), the Gambia (Blimpo, Evans, & Lahire, 2011), and Niger (Beasley & Huillery, 2017) show no improvement on student learning outcomes. In contrast, experimental evidence from Indonesia (Pradhan et al, 2014) and Kenya (Duflo, Dupas, & Kremer, 2015) find significant, positive effects on student test scores.…”
Section: Introductionmentioning
confidence: 92%
“…Despite the widespread adoption of SBM, the effectiveness of these programs in raising educational outcomes have been mixed. Experiments in India (Banerjee et al, 2010), the Gambia (Blimpo, Evans, & Lahire, 2011), and Niger (Beasley & Huillery, 2017) show no improvement on student learning outcomes. In contrast, experimental evidence from Indonesia (Pradhan et al, 2014) and Kenya (Duflo, Dupas, & Kremer, 2015) find significant, positive effects on student test scores.…”
Section: Introductionmentioning
confidence: 92%
“…Most empirical studies of SBM effectiveness instead focus on its effects on educational outcomes, including both intermediate indicators, such as attendance, retention, and grade passing rates, and final outcomes in educational attainment, usually measured by increases in test scores (Blimpo, Evans, & Lahire, 2011;Jimenez & Sawada, 1999;Jimenez & Sawada, 2014;Ling et al, 2010). A recent systematic review of the effects of SBM on educational outcomes in lowand middle-income countries concluded that the effects on student attendance and dropout were weak and sometimes inconsistent but that SBM tended to have negative significant effects on grade repetition and positive significant effects on test scores ranging between 0.10 and 0.20 standard deviations (Carr-Hill et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Giving school committees the authority to procure materials at local level potentially aids efficiency and yields cost savings that can be deployed for other school improvements, while allowing schools to make local decisions enables them to avoid waste by purchasing the inputs they actually require to meet student needs (Gershberg, Meade, & Andersson, 2009). Improvements in the provision of school resources and inputs also stem from the fact that school committees are often able to harness contributions in cash and kind from local communities (Blimpo et al, 2011;Patrinos et al, 2009). Masue and Askvik (2017) noted that one of the key objectives of school committees in Tanzania is to mobilize voluntary community contributions for school projects, Yamada (2014) observed that school committees in Ethiopia mobilized funds for school improvement via collective cultivation of school farms and the collection and sale of wood and grass, and Gershberg et al (2009) documented that parents in community-managed Guatemalan schools were expected to contribute their labor to school construction and maintenance projects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…evidence on the effectiveness of local committees in improving school management and performance is, at best, mixed. For example, some studies highlight that giving autonomy to school-level actors has a positive impact on process outcomes, such as improved community involvement in schools, but has no impact on student achievement (Beasley & Huillery, 2017;Blimpo, Evans, & Lahire, 2011). Other studies, however, show positive effects of engagement with school committees on test scores (Duflo, Dupas, & Kremer, 2015), while some studies show no effect on intermediate or longer-term outcomes (Banerjee, Banerji, Duflo, Glennerster, & Khemani, 2008).…”
Section: Theoretical Framework and Prior Evidencementioning
confidence: 99%